2013
DOI: 10.1007/s00277-013-1913-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the duration of antiviral prophylaxis on rates of varicella-zoster virus reactivation disease in autologous hematopoietic cell transplantation recipients

Abstract: Varicella-zoster virus (VZV) reactivation is a relatively common cause of morbidity following autologous hematopoietic cell transplant (auto-HCT). The Centers for Disease Control in 2009 recommended extending VZV prophylaxis for 1 year post-transplantation. We retrospectively analyzed rates of VZV reactivation following auto-HCT at our transplant center prior to and after the implementation of extended antiviral prophylaxis in June 2008. The study population was divided into three different cohorts according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…On the other hand, VZV disease occurs in approximately 16-28 % without long-term prophylaxis [2][3][4][5] and typically presents as a localized dermatomal rash. In addition, disseminated VZV disease, which can result in a fatal outcome [6], and various complications including postherpetic neuralgia and secondary bacterial infections are sometimes observed and may influence the patient's quality of life [2][3][4][5]7]. Therefore, to reduce HSV and VZV disease and their complications, acyclovir prophylaxis has been assessed in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, VZV disease occurs in approximately 16-28 % without long-term prophylaxis [2][3][4][5] and typically presents as a localized dermatomal rash. In addition, disseminated VZV disease, which can result in a fatal outcome [6], and various complications including postherpetic neuralgia and secondary bacterial infections are sometimes observed and may influence the patient's quality of life [2][3][4][5]7]. Therefore, to reduce HSV and VZV disease and their complications, acyclovir prophylaxis has been assessed in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing use of novel chemotherapeutic regimens, T-cell depleting agents (e.g., CD34 selection, Thymoglobulin) and biologics, and maintenance therapies, along with an aging HCT population, poses a heightened risk for infections in this patient population 15 . Studies have reported herpes zoster (HZ) as a common infectious complication after autologous HCT in 16%-30% of patients, with most events occurring in the first year after HCT 6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the typical presentation of HZ with a painful dermatomal rash, HCT recipients often experience complications such as post-herpetic neuralgia, ocular disease, and potentially fatal disseminated disease in one-third or more of affected patients 5,914 . Given the significant advances in the treatment and supportive care for autologous HCT recipients over the past decade, including the increased use of novel drugs for maintenance therapy after HCT (e.g., bortezomib, lenalidomide) 1,2 , a contemporary understanding of the long-term risk of HZ in this population is important.…”
Section: Introductionmentioning
confidence: 99%
“…Truong et al [23] carried out a retrospective chart review study among 129 patients undergoing auto-HSCT between January 1, 2004 and January 31, 2010 to analyze rates of VZV reactivation in three different cohorts according to the length of VZV prophylaxis: (1) prophylaxis until neutrophil recovery to ≥500/μL ( n  = 77), (2) prophylaxis for 6 months ( n  = 12), or (3) 12 months ( n  = 40) after auto-HSCT procedure. They found that a significant reduction in rates of VZV reactivation with extended 12-month antiviral prophylaxis (2%) compared to the neutrophil recovery (14%) ( p  = 0.04).…”
Section: Discussionmentioning
confidence: 99%